Comparative analysis of Passivhaus simulated and measured overheating frequency in a typical dwelling in Ireland. Issue 6 (17th August 2020) - Finegan, Evan; Kelly, Gerard; O'Sullivan, Garrett
ABSTRACT: Passive House Planning Package (PHPP) simulations are crucial in balancing a reduced space heat demand and reduced overheating in Passivhaus dwellings. This paper identifies the PHPP simulated overheating frequency (OF) for a dwelling in Douglas, Cork, Ireland, constructed in 2015. The measured indoor temperature is also recorded over a 12-month period. A comparative analysis of measured and simulated overheating is carried out, with two overheating thresholds of 25°C and 24°C. The simulation estimates an OF of 0.00%, for a typical year (at 25°C). The simulation relies on a dwelling average temperature, where the equivalent measured OF for the test year is 2.64%, derived from a volume-weighted mean indoor temperature ( T vm ). At a reduced threshold of 24°C, the measured OF is 4.67%. Measurements within 6 independent zones identify 52.61% of readings above 25°C are eliminated by using T vm . The representation of overheating as a percentage of the year is shown to distort the effect of overheating, while the T vm value overlooks variations in zonal temperature. This paper recommends that a more robust assessment tool is developed within PHPP, to predict OF for passive house dwellings, while adopting this methodology for dwellings of Nearly Zero Energy Buildings (nZEB) standard.